The smoke at dawn [compact disc, unabridged] : a novel of the Civil War - Shaara, Jeff, 1952- (Civil War series, 2014)
Summer, 1863. The Federal triumph at Vicksburg has secured complete control of the Mississippi River from the Confederacy, cementing the reputation of Ulysses S. Grant. Farther east, the Federal army under the command of William Rosecrans captures the crucial rail hub at Chattanooga. But Rosecrans is careless, and while pursuing the Confederates, the Federal forces are routed in north Georgia at Chickamauga Creek. A disgusted Abraham Lincoln has seen enough of General Rosecrans.